Sulfuric Acid Resistance of Geopolymer Mortars from Co-combustion Residuals of Bamboo and Kaolin - Aprilina Purbasari; Tjokorde Walmiki Samadhi; Yazid Bindar (Department of Chemical Engineering, Universitas Gadjah Mada, 2019)
This study presents an investigation of the durability and microstructure of geopolymer mortars from co-combustion residuals of bamboo and kaolin when exposed to 5% sulfuric acid solution for 2, 4, and 6 weeks, respectively. Geopolymer mortars sized 5 x 5 x 5 cm were prepared from co-combustion residuals of bamboo and kaolin with alkaline activators, i.e. mixture of 10 N potassium hydroxide solution and sodium silicate solution, and cured at 60 oC in oven for 8 hours and then at room temperature for 28 days. Mortars from ordinary Portland cement were also prepared as control mortars. The parameters studied were visual appearance changes, mass changes, compressive strength changes, and microstructure changes. Microstructure changes were examined using Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), and scanning electron microscopy (SEM). The results revealed that geopolymer mortars showed better sulfuric acid resistance compared to ordinary Portland cement mortars in terms of lower mass loss and lower compressive strength loss.